Skill composition of immigration flows and the measurement of education-occupation mismatch - Jacques Poot; Steven Stillman (IZA Journal of Migration, 2016)
Recent papers have found that often immigrants are overqualified relative to native-born workers when comparing an individual's education to the 'average' education in their occupation. We show that these results are sensitive to differences in the education distribution between immigrants and the native born. Using data for New Zealand, which has an immigration policy that favours skilled immigrants, we find that this approach leads one to conclude that immigrants are, on average, overqualified for their occupation. However, once we account for the fact that immigrants are on average more skilled than natives, we find that immigrants are, in fact, less overeducated than natives.
Keywords: F22; J21; J61; 330; Immigration; Occupation; Skill transferability; Job-worker mismatch; Discrimination; New Zealand